2015
DOI: 10.5588/ijtld.14.0348
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and incidence of tuberculosis among contacts of pulmonary tuberculosis patients

Abstract: A prospective cohort study was conducted from 2009 to 2012 to assess the relationship between serum baseline 25-hydroxivytamin D (vitamin D) status and the incidence of tuberculosis (TB) among 572 contacts of 89 pulmonary TB patients in Castellon, Spain. Three new cases of pulmonary TB occurred, with an incidence density of 3.6 per 1000 person-years. Mean vitamin D status was 13.7 ng/ml for cases and 25.7 ng/ml for non-cases. Vitamin D status showed a significant inverse association with TB incidence (adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…Although this finding can reflect a state of ill health or wasting secondary to a chronic infection [32] it may also support the hypothesis that low VD levels confers higher risk of progression from LTBI to active TB [33]. Consistent with our findings, other authors have shown that hypovitaminosis D can be regularly found in subjects with active TB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although this finding can reflect a state of ill health or wasting secondary to a chronic infection [32] it may also support the hypothesis that low VD levels confers higher risk of progression from LTBI to active TB [33]. Consistent with our findings, other authors have shown that hypovitaminosis D can be regularly found in subjects with active TB.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Arnedo-Pena et al . showed in a prospective cohort study a significant inverse association between VD status at baseline and TB incidence at long term follow up (HR 0.88, 95% CI 0.80–0.97), although no further VD measurements were done beyond baseline [33]. In Pakistan, a cohort study of HHC of pulmonary TB patients also found that VD deficiency was a risk factor for developing active TB (RR 5.1 95% CI 1.2–21.3) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 15 articles published from 1985 through 2014 were included for further analysis. [ 6 – 10 , 20 29 ] These 15 eligible studies included 1440 cases and 2558 controls. Eight [ 6 – 10 , 20 22 ] of them only involved Asian participants and two [ 23 , 24 ] only involved African subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding further indicates that severe vitamin D deficiency in HIV patients is a risk factor for the development of active TB. [40,43] …”
Section: Discussionmentioning
confidence: 99%